Pengaruh Pendidikan dan Motivasi Kewirausahaan Terhadap Keberhasilan Usaha Butik Di Pasar Petisah Kota Medan - Rizqina, Alfi; Siregar , Dahrul (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The purpose of this study was to determine the effect of entrepreneurship education and motivation on the success of boutique businesses in Pasar Petisah, Medan City. This type of research is associative research. The population of this study were boutique business owners in Pasar Petisah, Medan City. The data analysis technique used was a quantitative method with the help of the SPSS program. This study used multiple linear regression, partial tests and simultaneous tests. The sample in this study was 150 respondents. Primary data collection used a questionnaire. The results showed that entrepreneurship education partially had a positive and significant effect on the success of boutique businesses in Pasar Petisah, Medan City, where t count 8.103> t table 1.976 and significant 0.000 <0.05. Entrepreneurial motivation partially had a positive and significant effect on the success of boutique businesses in Pasar Petisah, Medan City, where t count 14.828> t table 1.976 and significant 0.000 <0.05. Entrepreneurship education and entrepreneurial motivation simultaneously have a positive and significant effect on the success of boutique businesses in Petisah Market, Medan City, where F count 403.124 > F table 3.06 and significant 0.000 < 0.05.